2005
DOI: 10.1093/hmg/ddi223
|View full text |Cite
|
Sign up to set email alerts
|

Altered mRNA splicing of the skeletal muscle ryanodine receptor and sarcoplasmic/endoplasmic reticulum Ca2+-ATPase in myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1) is a debilitating multisystemic disorder caused by a CTG repeat expansion in the DMPK gene. Aberrant splicing of several genes has been reported to contribute to some symptoms of DM1, but the cause of muscle weakness in DM1 and elevated Ca2+ concentrations in cultured DM muscle cells is unknown. Here, we investigated the alternative splicing of mRNAs of two major proteins of the sarcoplasmic reticulum, the ryanodine receptor 1 (RyR1) and sarcoplasmic/endoplasmic reticulum Ca2+-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
260
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(280 citation statements)
references
References 45 publications
16
260
0
4
Order By: Relevance
“…To assess the downstream effect of expanded CUG transcript degradation on aberrant splicing, we examined the alternative splicing of three DM1-associated splicing events: Cypher, Serca1, and Clcn1 (20)(21)(22). At time points more than 2 wk after tamoxifen injection, all three events reverted toward the embryonic splicing pattern as expected (Fig.…”
Section: Cag Gapmers Induce Degradation Of Expanded Dmpk Transcripts Inmentioning
confidence: 54%
“…To assess the downstream effect of expanded CUG transcript degradation on aberrant splicing, we examined the alternative splicing of three DM1-associated splicing events: Cypher, Serca1, and Clcn1 (20)(21)(22). At time points more than 2 wk after tamoxifen injection, all three events reverted toward the embryonic splicing pattern as expected (Fig.…”
Section: Cag Gapmers Induce Degradation Of Expanded Dmpk Transcripts Inmentioning
confidence: 54%
“…The longer t EMG-MMG in DM1 may be explained by the alteration in the splicing of several proteins, such as SERCA1 and CACNA1S, involved in Ca 2+ homeostasis and in excitation-contraction coupling mechanism [6][7][8][9][10] thus possibly leading to a lengthened duration of the dihydropyridine and ryanodine receptors interaction, Ca 2+ release by sarcoplasmic reticulum, and troponin activation [9,10,35].…”
Section: Delays During Muscle Contractionmentioning
confidence: 99%
“…Experimental evidence demonstrates that an alteration in the splicing of several proteins involved in Ca 2+ homeostasis and in excitation-contraction coupling mechanisms may play a pivotal role [6][7][8][9][10]. Myotonia is characterised by a state of pathologically enhanced muscle excitability, in which involuntary trains of action potentials cause a delay in muscle relaxation after contraction [11].…”
Section: Introductionmentioning
confidence: 99%
“…26 However, thus far, no direct evidence demonstrated that the splicing misregulation of INSR and TNNT2 genes leads to, respectively, insulin resistance and conduction defects in DM1. Several other pre-mRNA transcripts regulated by MBNL1 and CUGBP1 proteins are aberrantly spliced in DM1, such as sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase 1 (ATP2A1, also known as SERCA1), 48 ryanodine receptor (RyR), 48 fast skeletal troponin T (TNNT3), 49 and myotubularin-related protein 1 (MTMR1). 50 Data that support the involvement of MBNL1 and CUGBP1 splicing factors in DM1 pathogenesis come from mouse models that have recapitulated DM splicing patterns and related skeletal and cardiac muscle abnormalities through either gene knock-out of Mbnl1, 49 or transgenic overexpression of CUGBP1.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%